Climate change impacts to coastal communities in Kudat, Sabah, Malaysia - Nurrul Fazlina Osman; Ejria Saleh; Nurulain Ismail; Justin Sentian; Madihah Jafar Sidek (Secholian Publication, 2022)
Climate change is the among major threats to marine ecosystems, representing both a challenge and an opportunity for researchers and the government. Impacts are not experienced uniformly, and the existing unbalanced ecosystems will be further exacerbated without urgent action to mitigate climate change and enhance community resilience. The objective of this study is to draw insights on the impact of climate change based on the coastal community input and environment change at Kimihang, Kelambu Beach and Bavang Jamal, Kudat, Sabah. Interviews and fieldwork were carried out in March and August 2020. The unstructured questionnaire was applied to 15 respondents to know in-depth experiences on the impacts of climate change. The data were presented as timeline narration before and after the year 2000. Results show that the respondents addressed climate change through the reduction of natural resources yields, and change of surrounding environment, career paths of the young generation, and the existence of structural management. The coastal communities were found to have lacked the know-how and awareness to manage and maximized the use of their coastal resources sustainably. This is to suggest that constructing the best adaptation strategies requires attention in this region.